“Membimbing dengan Media, Konseling dengan HATI” untuk Pengembangan Jati Diri Siswa - Maria Patricia Tjasmadi (Universitas Mathla'ul Anwar Banten, 2019)
“GUIDANCE WITH MEDIA, COUNSELING WITH HATI” FOR STUDENT IDENTITY DEVELOPING. The Industrial Revolution 4.0 is feared to have a significant impact, where the role of machines or robots will replace the work and role of humans. The explosion of unemployment and the destruction of the existing work system, towards the threshold of extinction. Therefore, Guidance and Counseling Services in the era of the Industrial Revolution 4.0 is a complex challenge that must be addressed optimistically because artificial intelligence robots will not replace this service field. The acceleration of technology and digital products in this era predicted to make many people put forward emotion more than empathy. A relaxed and comfortable lifestyle will be inversely proportional if expectations do not match reality. Guidance and Counseling Services will be increasingly expected to be able to anticipate the situation of those who experience cognitive distortions. Research on instructional media in Guidance and Counseling services with the theme Guiding with Media, Counseling of HATI proves that the role of Guidance and Counseling Teachers is still very much needed in the era of the Industrial Revolution 4.0.